Hypothyroidism, Hyperthyroidism and its Relationship with Lipid Profile in Thyroid Dysfunction Patients (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: -Thyroid hormone synthesis is necessary for the growth, development, and healthy function of all body organs. Because thyroid malfunction causes a considerable shift in lipid levels, It is well known that thyroid hormones influence how lipid and lipoprotein metabolism is regulated. An essential regulator of intermediate metabolism are thyroid hormones. The purpose This study's objective was to look at the relationship between thyroid dysfunction patients' lipid profiles, hypothyroidism, and hyperthyroidism ..Materials and Methods:-In this study, the EIA method was used to evaluate the levels of T4, thyronine, and TSH in a sample of 50 patients and 50 healthy individuals. When assessing TG, LDL , TC ,and HDL , A fully automated biochemistry analyzer was employed.Results:-According to our research, HDL values are much lower in hypothyroidism cases compared to hyperthyroidism and control subjects, whereas TC, LDL, VLDL, and TG levels are significantly greater. When compared to control persons. Serum levels of, TG, TC, LDL, and VLDL are much lower in hyperthyroidism patients On the basis of a clinical examination of thyroid hormone., we found T4,T3 in serum sample  wear higher than  in control in hyperthyroid group while TSH wear low.  In hypothyroid sample we found on the contrary .Conclusion:-In this research we found a significant correlation between thyroid dysfunction and lipid profile